2007
DOI: 10.1111/j.1439-0531.2007.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in the Water Buffalo

Abstract: In this paper, an account of various aspects related to buffalo reproduction are given. Fundamental concepts of the reproductive physiology as well as manipulation of the reproductive function will be presented. This will include an overview of the most recent developments of the oestrous cycle and the ovulation control, new strategies of reproductive management for the improvement of genetic gain and the application of newly developed reproductive technologies, such as in vitro embryo production, embryo and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 89 publications
(170 reference statements)
1
22
1
Order By: Relevance
“…Consequently, the inter-calving period was increased in these buffaloes. These observations are in agreement with those of other studies that have reported that buffalo cows exhibit a longer postpartum anoestrus during days with increasing daylength (Presicce et al 2004;Presicce 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, the inter-calving period was increased in these buffaloes. These observations are in agreement with those of other studies that have reported that buffalo cows exhibit a longer postpartum anoestrus during days with increasing daylength (Presicce et al 2004;Presicce 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In practice, heifers are usually mated from March to August, while multiparous buffaloes are mated from March to October. The greatest milk price (generally +30% compared to the rest of the year) [28] paid to farmers when the market demand is maximum (from late spring to late summer) counteracts the economic losses, due to the suboptimal fertility faced in the off-breeding period [23]. The least square means for the fixed effect of month of calving (Table 3) revealed small variability for most of the milk composition traits.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Currently, the retrieval of oocytes through the use of ultrasound guided follicle puncture, or ovum pick-up (OPU), is inescapably linked to the procedures for in vitro embryo production, as it can exploit the most elite males and females to combine for an accelerated genetic gain [14]. Ovum pick-up has been shown to be a valuable technology greatly enhancing the potential of IVF systems in a variety of breeding conditions and species [8, 1519]. Since its initial development, a number of interesting aspects have arisen highlighting, for example, the donor cow effect on oocyte retrieval and in vitro embryo production [20].…”
Section: Introductionmentioning
confidence: 99%